THE ROLE OF ARTICLE 28C PARAGRAPH (1) OF THE 1945 CONSTITUTION IN GUARANTEEING ACCESS TO EDUCATION AND CULTURAL DEVELOPMENT IN INDONESIA - Gunawan Widjaja (International Journal of Teaching and Learning, 2025)
This study aims to examine the role of Article 28C Paragraph (1) of the 1945 Constitution in guaranteeing access to education and cultural development in Indonesia. This article stipulates the right of every person to develop themselves through the fulfilment of their basic needs, including education and culture, as part of their human rights that must be protected by the state. The research method used is qualitative through the analysis of legal documents, education and cultural policies. The results show that Article 28C Paragraph (1) is an important constitutional basis that guides government policy in providing equitable and inclusive access to education and supporting the preservation and development of culture. However, in its implementation, there are still various challenges, such as inequality in access to education and a lack of attention to cultural diversity. This study recommends strengthening the synergy between the government and the community in order to optimise the role of this article in realising quality human resource development and sustainable cultural preservation in Indonesia.